Yeast On Epiphyte of Tangerines Citrus Fruit (Citrus nobilis L.) and Their Potential Antagonist to Colletotrichum Gloeosporioides (Penz.) Penz. & Sacc. - Pramudita, Oki; Muhibuddin, Anton (Inscientech: Journal of Industrial, Science and Technology, 2017)
One of the most important diseases of citrus plant is anthracnose which caused by Colletotrichum gloeosporioides (Penz.) fungi. Yeast is one of microbes which has a good potential to control the disease. This research focused on exploring yeasts on tangerines and examining their efficacy to control C. gloeosporioides using in vitro and in vivo treatments. Observation was started by isolated C. gloeosporioides and yeast from tangerines citrus fruit, then followed with in vitro and in vitro treatment. Both were counted the percentage of antagonist and pathogen incubation stage and also disease incidence, respectively. Result showed that yeast has been isolated from tangerines fruit were Candida sp. (isolate 1), Candida sp. (isolate 2) and Pichia sp. All yeast showed inhibit C. gloeosporioides growth and suppressed its development.